Genetic analysis and morphological identification of pilus-like structures in members of the genus Bifidobacterium - Zhang Ziding; Viappiani Alice; O’Connell Motherway Mary; Bottacini Francesca; He Fei; Turroni Francesca; Amidani Davide; Serafini Fausta; Foroni Elena; Rivetti Claudio; van Sinderen Douwe; Ventura Marco (Microbial Cell Factories, 2011)
Abstract Background Cell surface pili in Gram positive bacteria have been reported to orchestrate the colonization of host tissues, evasion of immunity and the development of biofilms. So far, little if any information is available on the presence of pilus-like structures in human gut commensals like bifidobacteria. Results and discussion In this report, Atomic Force Microscopy (AFM) of various bifidobacterial strains belonging to Bifidobacterium bifidum, Bifidobacterium longum subsp. longum, Bifidobacterium dentium, Bifidobacterium adolescentis and Bifidobacterium animalis subsp. lactis revealed the existence of appendages resembling pilus-like structures. Interestingly, these microorganisms harbour two to six predicted pilus gene clusters in their genome, with each organized in an operon encompassing the major pilin subunit-encoding gene (designated fimA or fimP) together with one or two minor pilin subunit-encoding genes (designated as fimB and/or fimQ), and a gene encoding a sortase enzyme (strA). Quantitative Real Time (qRT)-PCR analysis and RT-PCR experiments revealed a polycistronic mRNA, encompassing the fimA/P and fimB/Q genes, which are differentially expressed upon cultivation of bifidobacteria on various glycans.